Analysis of the Use of Non-Invasive Lung Ventilation Support in Newborns and Young Children after Cardiac Surgery - Olena O. Yakimishen; Olena I. Tsymbal; Serhii M. Boiko; Iaroslav P. Truba (Ukrainian Journal of Cardiovascular Surgery, 2023)
Background. Non-invasive ventilatory support for artificial lung ventilation (ALV) in infants with congenital heart disease after cardiac surgery helps to reduce the duration of invasive ALV, reduce the number of mechanical and infectious complications, and reduce or eliminate the need for sedation.The aim. To analyze the experience of using non-invasive ventilatory support after surgical correction of congenital heart disease in infants and compare its effectiveness with invasive mechanical ventilation.Materials and methods. We conducted a retrospective analysis of the use of non-invasive ALV and its effectiveness compared to invasive mechanical ventilation in children under 1 year of age after cardiac surgery from 2020 to 2022 at the Department of Cardiac Arrest in Newborns and Young Children of the National Amosov Institute of Cardiovascular Surgery of the National Academy of Medical Sciences of Ukraine. During this period, 134 patients were operated on (38 children under 1 month old, 96 children under 1 year old). In the postoperative period, 85 children (55.9%) needed prolonged mechanical ventilation (more than 24 hours), of which non-invasive ventilation support was used in 32 patients (37.6%) and invasive ventilation in 53 (62.3%) patients.Results. The patients on non-invasive ALV (n = 32) had lower weight (p = 0.23), shorter ventilation time (p = 0.56), and the time spent at the intensive care unit (p = 0.61), required less sedation (p = 0.29), and had lower mortality (p = 0.42) compared to the group of children who received only invasive ventilatory support (n = 53), but this difference was not statistically significant. The need for non-invasive ventilation was higher in 9 (28.12%) infants than in 8 (15.09%) other infants and was statistically significant (p < 0.001).Conclusions. Our study showed that the use of non-invasive ALV can shorten the length of stay at the intensive care unit and the time spent on ventilation, reduce or avoid the use of sedation, and prevent pulmonary complications (infectious and mechanical) with long-term treatment. However, there was no significant difference between non-invasive and invasive ventilation in terms of mortality.